2012
DOI: 10.12669/pjms.291.1971
|View full text |Cite
|
Sign up to set email alerts
|

BAL for pneumonia prevention in tracheostomy patients: A clinical trial study

Abstract: Objective: To evaluate the role of flexible bronchoscopy (FB) and bronchoalveolar lavage (BAL) on pneumonia prevention of tracheostomy patients in intensive care unit. Methodology: This clinical trial was conducted on 67 head-injury patients who needed tracheostomy. The eligible patients were divided into two groups of different methods for removing the airway secretions. In intervention group, FB and BAL was added to routine conventional methods for airway clearance. Patients were followed for signs and sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Various complications reported include oxygen desaturation (3%–65%), bleeding (2.4%–32.4%), arrhythmias (1.5%–5.7%), bronchospasm (1.9%–8.6%), pneumothorax (1.2%–23.6%), hypotension (2.5%–22%), increased intracranial tension (20%–81%), and death (0.8%–5.4%). [379380384385386388403404405406407408409410411412] In a prospective evaluation of 107 critically ill patients who underwent bronchoscopy (73 on invasive mechanical ventilation, 28 on oxygen, 6 on NIV), 10 patients had reversible cardiorespiratory events and 13 patients had transient desaturation. [380] While performing endobronchial sampling in the ICU, complications such as oxygen desaturation, hemorrhage, arrhythmias, bronchospasm, and pneumothoraces have been reported.…”
Section: Flexible Bronchoscopy In Intensive Care Unit (Icu)mentioning
confidence: 99%
“…Various complications reported include oxygen desaturation (3%–65%), bleeding (2.4%–32.4%), arrhythmias (1.5%–5.7%), bronchospasm (1.9%–8.6%), pneumothorax (1.2%–23.6%), hypotension (2.5%–22%), increased intracranial tension (20%–81%), and death (0.8%–5.4%). [379380384385386388403404405406407408409410411412] In a prospective evaluation of 107 critically ill patients who underwent bronchoscopy (73 on invasive mechanical ventilation, 28 on oxygen, 6 on NIV), 10 patients had reversible cardiorespiratory events and 13 patients had transient desaturation. [380] While performing endobronchial sampling in the ICU, complications such as oxygen desaturation, hemorrhage, arrhythmias, bronchospasm, and pneumothoraces have been reported.…”
Section: Flexible Bronchoscopy In Intensive Care Unit (Icu)mentioning
confidence: 99%
“…Previous studies have shown beneficial rule for bronchoscopic suction of secretions in preventing the development of pneumonia; Vejdan and Khosravi demonstrated in their clinical trial that the use of FB and BAL to clear airway secretions in head trauma patients who needed tracheostomy decreased the risk of nosocomial pneumonia from 35 to 14% and can even shorten the ICU stay time. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, Ellekjaer et al 6 found that prophylactic bronchoscopy provided no benefit in critically ill patients with acute respiratory failure. On the other hand, Vejdan et al 7 reported that the use of prophylactic bronchoscopy and bronchoalveolar lavage significantly reduced the risk of nosocomial pneumonia in tracheostomy patients. Although prophylactic flexible bronchoscopy clearly shows benefit in some situations, it may not always be advisable.…”
Section: Discussionmentioning
confidence: 99%